Defining children's stories through narrative structure an analysis of selected short stories by Gemma Cruz, Ma. Elena Paterno, and Alfred Yuson - Teodosio, Sharon Fiel Ramirez
This thesis validates Chatman's method of analyzing narrative structure as applied to thre short stories for children. These are Gemma Cruz's "Makisig, the Little hero of Mactan (1964), Ma. Elena Paterno's The Boy Who Listened to the Sea (1990) and Alfred Yuson's The boy Who ate stars (1993). The analysis here describes the narrative structure by identifying the distributive and integrative functions of each text. This is accomplished on two levels. First, in terms of the character or trait and the story's atmosphere. Second, in terms of the generic narrative structure in children's stories. The study reveals that patterns of generic narrative as well as character trait and story's atmosphere are the elements which differentiate stories for children thus justifying its autonomy as a discipline.